The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1007/s10552-017-0993-9
|View full text |Cite
|
Sign up to set email alerts
|

Trends in prostate cancer incidence between 1996 and 2013 in two Swiss regions by age, grade, and T-stage

Abstract: The trends in prostate cancer incidence rates were similar in both regions, although on a higher level in Zurich compared to Ticino. However, the difference decreased over time. The distribution of T-stage and grade did not explain the difference in incidence rates. Different use of opportunistic screening may play a role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Changes towards less PSA screening in Switzerland may have occurred before this recommendation. Our finding concurred with a recent regional Swiss study which reported an increase in incidence of prostate cancer in men aged under 65 years in the canton of Zurich up to 2002 and in canton of Ticino up to 2007, followed by a decline [23]. If this trend were to continue in Switzerland, the incidence of early-stage prostate cancer could decrease.…”
Section: Discussionsupporting
confidence: 92%
“…Changes towards less PSA screening in Switzerland may have occurred before this recommendation. Our finding concurred with a recent regional Swiss study which reported an increase in incidence of prostate cancer in men aged under 65 years in the canton of Zurich up to 2002 and in canton of Ticino up to 2007, followed by a decline [23]. If this trend were to continue in Switzerland, the incidence of early-stage prostate cancer could decrease.…”
Section: Discussionsupporting
confidence: 92%
“…An increase in incidence is supported by data from the French-speaking part of Switzerland for the period from 1974 until at least 1994 (canton of Vaud) [21], and from 1973 until about 2000 (canton of Geneva) [22]. Increasing incidence was also observed in the Italianspeaking part of Switzerland from 1996 until 2007 [12], even though the rates in these regions were considerably lower. The latter study was a comparison of prostate cancer incidence between Zurich and Ticino for the period 1996 to 2013 [12].…”
Section: Comparison With Other Studiesmentioning
confidence: 75%
“…Increasing incidence was also observed in the Italianspeaking part of Switzerland from 1996 until 2007 [12], even though the rates in these regions were considerably lower. The latter study was a comparison of prostate cancer incidence between Zurich and Ticino for the period 1996 to 2013 [12]. A strong increase in incidence from the 1970s or 1980s, up to around 2000-2005 and levelling off afterwards, was reported in other European countries [23,24].…”
Section: Comparison With Other Studiesmentioning
confidence: 90%
See 1 more Smart Citation
“…Before the 1980s, the incidence of prostate cancer in China was less than 1/100,000, and the incidence was extremely low, but after decades of change, the incidence of prostate cancer has now exceeded 5/100,000, and it is skyrocketing, nearly fivefold to the original. Specifically, the incidence of prostate cancer registered in China in 2012 was 9.92/100,000; the sixth highest incidence of malignant neoplasms in men, and in 2018, prostate cancer patients in Asia accounted for 18,100,001 and half of the world's new patients [12,13].…”
Section: Introductionmentioning
confidence: 99%